Management of Locked Volar Radio-ulnar Joint Dislocation. Issue 10 (October 2019) - Starnoni, Marta; Colzani, Giulia; De Santis, Giorgio; Leti Acciaro, Andrea
Abstract : Summary: Isolated volar dislocation of the distal radio-ulnar joint is an extremely rare lesion. Diagnosis is commonly missed. The authors report their experience about a case of an acute locked volar distal radio-ulnar joint dislocation. A correct clinical and radiological diagnosis was done in the Emergency Department, and a closed reduction was achieved only after an axillary block, after a first failed attempt under slight sedation. A K-wire blocking the prono-supination and a short removable forearm cast protected the reduction for 25 days. Two weeks after the removal of the immobilization, the patient presented a complete functional recovery, with full range of motion. The authors highlight the importance of the clinical and radiological findings: a dorsal dimple at the ulnar side leads to a high index of suspicion, and represent the most relevant aid in diagnosis, associated to a proper imaging assessment. Prompt management allows a minimally invasive approach and a rapid functional recovery.